The potential of North Kalimantan's livestock sector as a buffer for the capital city of nusantara - Kurniawan Kurniawan; Borhan Sareya Abdullah; Karolus Sonu; Jubaidah Jubaidah (Faculty of Economics and Business, Universitas Mulawarman, 2023)
The potential of the livestock sector in North Kalimantan as a buffer for the capital of the Nusantara is interesting to be identified. Regional development and growing and sustainable business strategies in the livestock production sector have become complex and competitive between regions and business actors. Understanding the condition and potential of superior livestock and the economic life of workers in the livestock sector is crucial. Furthermore, it is a basis for developing and integrating policies that help livestock sector workers increase their production. This study aims to identify the leading commodities of the regency/city livestock sector in North Kalimantan to provide information to related parties and investors who are interested in the sector. North Kalimantan is one of the strategic provinces in Indonesia because it is located in the border area and is adjacent to the capital of the Nusantara. This study utilizes livestock data available from the North Kalimantan statistics for 2020 and 2021. Data analysis was carried out using the static location quotient. The results of data analysis explains that districts/cities in North Kalimantan have various types of superior livestock. Malinau regency has the leading livestock Pig (SLQ 2.03). Bulungan regency has superior livestock Beef cattle (SLQ 1.19) and Goats (SLQ 2.30). Nunukan regency has superior Beef cattle (SLQ 1,98), livestock Buffalo (SLQ 4.28) and Goat (SLQ 1.4). Tana Tidung regency and Tarakan city do not have superior livestock. North Kalimantan has the potential to support the capital of the Nusantara through the livestock sector.